2017
DOI: 10.3390/antiox6010009
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxybenzoic Acids Are Significant Contributors to the Antioxidant Effect of Borututu Bark, Cochlospermum angolensis Welw. ex Oliv

Abstract: Borututu (Cochlospermum angolensis) is an African tree whose bark has recently emerged as a herbal dietary supplement with claims for antioxidant activity. In order to substantiate the claimed activity of borututu supplements, we performed an activity-guided fractionation of the total extract utilizing a 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging assay. Subsequent flash and centrifugal chromatography resulted in the isolation of gallic acid (1) and protocatechuic acid (2) as the main antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
2
1
Order By: Relevance
“…The presence of ellagic acid, methyl ellagic acid and their glycosides (mainly hexosides and pentosides) as representative compounds of borututu root extracts has been previously reported [ 11 , 15 ]. Ferreres et al [ 11 ] did not find protocatechuic acid in the extract obtained by infusion with water, as opposed to what has been described in the present and other studies [ 8 , 15 ]. Moreover, the presence of rhamnose and galloyl residues in the ellagic and methyl ellagic acid glycosides has been identified for the first time in this study in borututu extracts.…”
Section: Resultscontrasting
confidence: 98%
See 3 more Smart Citations
“…The presence of ellagic acid, methyl ellagic acid and their glycosides (mainly hexosides and pentosides) as representative compounds of borututu root extracts has been previously reported [ 11 , 15 ]. Ferreres et al [ 11 ] did not find protocatechuic acid in the extract obtained by infusion with water, as opposed to what has been described in the present and other studies [ 8 , 15 ]. Moreover, the presence of rhamnose and galloyl residues in the ellagic and methyl ellagic acid glycosides has been identified for the first time in this study in borututu extracts.…”
Section: Resultscontrasting
confidence: 98%
“…Moreover, the presence of rhamnose and galloyl residues in the ellagic and methyl ellagic acid glycosides has been identified for the first time in this study in borututu extracts. Regarding gallic acid, in addition to the presence of galloyl forms, this compound was also found in its free form in the present study ( Table 3 ), which agrees with the findings of Abourashed and Fu [ 8 ], whereas Pereira et al [ 15 ] found this compound attached to the flavanol gallocatechin, thus forming gallocatechin gallate in borututu extracts.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations